Online consulting in general practice: making the move from disruptive innovation to mainstream service. (26th March 2018) - Marshall, Martin; Shah, Robina; Stokes-Lampard, Helen
Abstract : Services must be rigorously evaluated if we are to maximise benefits and minimise risks, say Martin Marshall and colleagues